Faktor-Faktor yang Berhubungan dengan Siklus Menstruasi pada Wanita Usia Subur: Literature Review - Dhiya Ulhaq, Ghina; Wittiarika, Ivon Diah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Menstruation is associated with sexual maturity, fertility, overall health, and even changes in various parts of the body. The menstrual cycle typically remains relatively stable during the reproductive years. However, 11.7% of adolescent girls in Indonesia experience menstrual cycle disturbances. Therefore, it is essential to identify factors related to the menstrual cycle. The study was a literature review. The literature used consisted of articles from national journals published in the last five years (2018–2023). The literature sources were obtained from "Google Scholar" using the keyword "siklus menstruasi".Five articles meeting the criteria were identified. Factors influencing the menstrual cycle in women of reproductive age included fast food consumption, stress levels, overweight or obesity, sleep quality, physical activity level, and anxiety. Conclusion: Effectively managing stress, maintaining an ideal body weight, ensuring an adequate amount of sleep, avoiding excessive physical activity, and addressing anxiety could contribute to a normal menstrual cycle.